2016
DOI: 10.1097/gme.0000000000000627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of walking on body composition in perimenopausal and postmenopausal women: a systematic review and meta-analysis

Abstract: Walking interventions improved body composition in perimenopausal and postmenopausal women, which underscores the central role of walking as a physical activity for health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…This is supported by RCTs that demonstrate that endurance training and strength training reduce blood pressure [ 21 23 ]. In addition, endurance training also reduces fat mass and abdominal circumference [ 22 , 24 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by RCTs that demonstrate that endurance training and strength training reduce blood pressure [ 21 23 ]. In addition, endurance training also reduces fat mass and abdominal circumference [ 22 , 24 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, endurance training and strength training have been shown to improve whole body insulin sensitivity [ 29 , 30 ]. Endurance training also reduces body weight in adults with normal weight, excess weight and obesity [ 1 , 22 , 24 , 25 , 31 , 32 ]. Finally, one specifically designed RCT has shown that physical activity reduces the risk of diabetes [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, continuous physical activity during the mid-life may be an efficacious strategy to counteract the age-related [ 166 ] and menopause-related decreases [ 89 ] in resting energy expenditure and prevent weight gain and abdominal adiposity deposition. In fact, a recently published meta-analysis of 8 walking intervention studies among peri- and postmenopausal women demonstrated statistically significant improvements in BMI, body weight, and body fat percentage as compared to no-exercise groups [ 167 ]. Further, recent work by Riou et al found that the quantity (i.e., amount of time spent) rather than the intensity of physical activity may be most efficacious strategy promoting lower adiposity and maintenance of body composition over the menopausal transition [ 168 ].…”
Section: Implications For Therapymentioning
confidence: 99%
“…8 Specifically in the elderly, the WHtR has better predictive ability than BMI and WC; 9 in addition, FP is an anthropometric indicator widely used in the literature. 10,11 In addition to the need of understanding the predictive ability of other measures to UI in older women, it is emphasized that regular physical activity has been reported as a protective factor for UI in this population, 12,13 which may favor another behavior pattern in the use of anthropometric measurements for UI.…”
Section: Introductionmentioning
confidence: 99%